Pengembangan Buku Petunjuk Praktikum Kimia Berbasis Learning Cycle 5E Sebagai Solusi dalam Masalah Pelaksanaan Praktikum Dirumah pada Masa Pandemi - elvy rahmi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Abstract. This research is based on existing problems, namely the absence of teaching materials that can support the implementation of the practicum and plus the learning process carried out during the covid-19 pandemic is learning at home or also called online learning, where students are instructed to study at home with use cell phone. This causes students to have difficulty understanding some chemical concepts. The purpose of this research is to produce a chemistry practicum manual based on learning cycle 5E for class XI SMAN 1 X Koto Diatas that can be used by students in carrying out practical activities at school and at home. This study uses a type of development research using a 4-D development model. The results showed that the validity of this 5E learning cycle-based chemistry practicum manual obtained a percentage of 96.00% with very valid criteria and the practicality results of this 5E learning cycle-based chemistry practicum manual obtained a percentage of 86.60% with very practical criteria. With this, it can be concluded that the chemistry practicum manual based on the 5E learning cycle that is designed is valid and can be used in the process of implementing the practicum.Keywords: Practicum Manual, Learning Cycle 5E, Validity and Practicality